Dimension of the Boundary in Different Metrics - Klén, Riku; Suomala, Ville (MATHEMATICA SCANDINAVICA, 2013)
We consider metrics on Euclidean domains $Ω\subsetR^n$ that are induced by continuous densities $ρ\colonΩ→(0,∞)$ and study the Hausdorff and packing dimensions of the boundary of $Ω$ with respect to these metrics.